Biomass pectin-derived N, S-enriched carbon with hierarchical porous structure as a metal-free catalyst for enhancing bio-electricity generation. (21st June 2019) - Ma, Yuanyuan; You, Shijie; Jing, Baojian; Xing, Zipeng; Chen, Hun; Dai, Ying; Zhang, Chunyue; Ren, Nanqi; Zou, Jinlong
Abstract: Heteroatoms-doped carbon-based materials (with non-precious metals or no metals) with porous structure have already shown high catalytic activities for oxygen reduction reaction (ORR), especially in microbial fuel cells (MFCs). Here, we use pectin extracted from pomelo peels as carbon source to prepare metal-free and sulphur/nitrogen co-doped partially-graphitized carbon (HP-SN-PGCs) by using silica nanospheres as sacrificial templates. Single-chamber MFC (SC-MFC) with HP-SN-PGC-0.5 (0.5 g of silica) cathode has the shortest start-up time (45 h) and lowest charge transfer resistance (19.3 Ω). The maximum power density of HP-SN-PGC-0.5 (1161.34 mW m −2 ) cathode is higher than that of Pt/C (1116.90 mW m −2 ) at the initial cycle. After 75 d operation, power density of HP-SN-PGC-0.5 cathode only declines 4.6%, which is more stable than that of Pt/C (37.69%). HP-SN-PGC-0.5 has a highly porous structure (869.25 m 2 g −1 ) by removal of templates and Fe species (as the graphitization catalyst) to facilitate exposure of active sites and diffusion of ORR-related intermediates (OH − and HO2 −, etc) to accessible active sites. N and S species provide highly active sites to enhance OH − generation to conduct the 4e − ORR process. Thus, this study presents a viable ORR catalyst with high activity and long-term stability for bio-electricity generation from organic wastewater in SC-MFCs. Graphical abstract: Image 1 Highlights: Pectin extracted from pomelo peels is used as carbon source for S, N co-doped carbon. Template strategy aids to form hierarchical porous carbon for smooth mass transfer. S and N species in carbon lattice have synergistic effects for boosting ORR activity. High activity and low H2 O2 yield guarantees the fast ORR kinetics via a 4e − pathway. Porous structure and defects of S, N co-doped carbon affords high property in SC-MFC.